Transferencias condicionadas y reducción de la pobreza en México: Entre lo real y lo imaginado - Banegas-González y Minor Mora-Salas, Israel; Mora-Salas, Minor (European Review of Latin American and Caribbean Studies, 2012)
Abstract: Conditional cash transfers and reduction of poverty in Mexico: Between reality and fantasyIn a longitudinal analysis, this study considers the changes in the well-being of beneficiary households of Mexico's conditional cash transfer (CCT) programme Oportunidades. Its objective is to assess whether this programme of cash transfers can contribute to sustained improvements in household well-being. The evidence shows that the aim of alleviating poverty is hard to achieve. Therefore, we argue that this CCT programme does not constitute an effective alternative for reducing structural vulnerability and poverty in the short term.Resumen:El estudio consiste en un análisis longitudinal sobre la evolución de las condiciones de vida de hogares beneficiarios del Programa Oportunidades-México. Tiene como propósito determinar en qué medida los programas de transferenci s económicas condicionadas propician procesos sostenidos de superación de la pobreza. El análisis demuestra que es muy difícil cumplir este acometido. En este sentido, se concluye que Oportunidades no constituye una alternativa eficiente para disminuir la vulnerabilidad estructural de los hogares pobres y para reducir la pobreza en el corto plazo.